2009
DOI: 10.1089/scd.2008.0097
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mesenchymal Stem Cells in the Functional Improvement of Chronic Renal Failure

Abstract: The most commonly used therapeutic targets in nephrology are the reduction of injury, the delay of progression, or renal replacement therapy. Many animal and human studies demonstrated the role of stem cells in repair and regenerations of kidney. Mesenchymal stem cells (MSCs) have shown to improve outcome of acute renal injury models. It is controversial whether MSCs can reduce injury following a toxic/ischemic event and delay renal failure in chronic kidney disease. We evaluated the hypothesis that the treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(101 citation statements)
references
References 32 publications
3
92
0
6
Order By: Relevance
“…In NZB/W F1 lupus mice treated with 1x10 6 human UC-MSCs via the tail vein, Chang and colleagues (Chang et al, 2011) found evidence of MSCs in kidney tissues at week 2 of infusion, but no long-term engraftment. Even if MSCs protect and improve recovery from several models of acute and chronic myocardial and renal injury (Humphreys and Bonventre, 2008;Choi et al, 2009), paracrine and endocrine eff ects seem most important, since conditioned medium from MSCs has been able to mimic the benefi cial eff ects of stem cell therapy (Bi et al, 2007).…”
Section: Msc Homing and Survivalmentioning
confidence: 99%
“…In NZB/W F1 lupus mice treated with 1x10 6 human UC-MSCs via the tail vein, Chang and colleagues (Chang et al, 2011) found evidence of MSCs in kidney tissues at week 2 of infusion, but no long-term engraftment. Even if MSCs protect and improve recovery from several models of acute and chronic myocardial and renal injury (Humphreys and Bonventre, 2008;Choi et al, 2009), paracrine and endocrine eff ects seem most important, since conditioned medium from MSCs has been able to mimic the benefi cial eff ects of stem cell therapy (Bi et al, 2007).…”
Section: Msc Homing and Survivalmentioning
confidence: 99%
“…Immunomodulation and paracrine action (32) Rat MSC, 1x10 5 cell/rat, e.v., 1 week after 5/6 nephrotomy MSC engraftment and paracrine action (33) Chronic Kidney Injury (unilateral ureteral obstruction)…”
Section: Animals Models Of Human Diseases: Kidney Heart Cns Livermentioning
confidence: 99%
“…The animals were selected randomly and kept in individual special plastic rodent cages in the laboratory under constant condition of temperature of 25 °C with a reverse natural dark-light cycle 12 [11] .…”
Section: Ratsmentioning
confidence: 99%
“…After 5 d, each animal was intravenously injected with MSCs extracted from male albino rats at a dose of 1伊10 6 cells per rat [12] .…”
Section: Ratsmentioning
confidence: 99%